Assessing bank stability through earnings capability and asset quality: Moderating impacts of institutions and taxation in Southeast Asia - Reni Listyawati; Fandi Galang Wicaksana; Prihatnolo Gandhi Amidjaya (JIFA (Journal of Islamic Finance and Accounting), 2026)
This study collects empirical information about the effect of Board of Directors (BOD) characteristics—specifically board size, age, tenure, and meeting frequency—on the timeliness of financial reporting, indicated by Audit Report Delay (ARD). We utilize a purposive sample of 430 firm-year observations from consumer-cyclical companies listed on the Indonesia Stock Exchange from 2018 to 2022. We analyze data from multiple years, using agency theory to look at relationships while considering factors like profitability, auditor reputation (Big Four versus non-Big Four), and the effects of the COVID-19 pandemic. The findings reveal that larger boards are associated with longer audit report delays, indicating that coordination inefficiencies may outweigh monitoring benefits. Conversely, more frequent board meetings are associated with shorter reporting delays, underscoring the role of active board engagement in enhancing reporting timeliness. Meanwhile, the average age of directors and the tenure of board membership had no significant impact on the timeliness of reporting. The research elucidates the specific board characteristics that most significantly influence disclosure efficiency, thereby informing directors and investors about optimal governance procedures. These insights enhance corporate governance literature by differentiating the roles of structural and demographic board aspects in expediting disclosures. Regulators and corporations in emerging markets should prioritize appropriate board composition—specifically size and meeting frequency—to enhance reporting timeliness, transparency, and stakeholder confidence during unpredictable economic conditions.